P-68 The impact of structured aerobic and resistance exercise on the course and outcomes of gestational diabetes mellitus: a randomised controlled trial. (18th November 2016) - Kokic, Iva Sklempe; Ivanisevic, Marina; Biolo, Gianni; Simunic, Bostjan; Kokic, Tomislav; Pisot, Rado
Abstract : To examine the effects of a structured, individualised, exercise programme consisting of aerobic and resistance exercises on the course and outcomes of gestational diabetes mellitus (GDM) since none of the previous trials investigated the effect of combination of these type of exercises. Thirty-eight pregnant women were randomly assigned to two groups: an experimental group, treated with standard care for GDM plus exercise therapy (EG; N = 18), and a control group (CG; N = 20) treated with standard care for GDM alone. A structured exercise programme was implemented from the time of diagnosis of GDM until the end of pregnancy, two times per week, with each session lasting 50-55 minutes. The women in the EG were also asked to undertake at least 30 minutes of brisk walking per day. At the end of the pregnancy we found lower postprandial glucose levels in EG compared to CG (P > 0.001, d = 1.38). No statistically significant differences were identified between the EG and CG in: the fasting glucose level at the end of pregnancy, the rate of complications in pregnancy and during labour and delivery, maternal body weight, maternal body fat percentage and weight gain during specific time periods of pregnancy, neonatal Apgar scores, neonatal body mass and ponderal index. Neonatal body mass index (BMI) was higher in the EG (P = 0.035, d = −0.76). No adverse side effects were encountered as a result of participating in the exercise programme. The exercise programme which was implemented had a positive effect on postprandial glucose levels at the end of pregnancy. In addition, no adverse side effects were reported, confirming that the structured exercise programme is a safe adjunctive therapy for GDM.